Dislocation-based interpretation on the effect of the loading frequency on the fatigue properties of JIS S15C low carbon steel. (January 2015) - Guennec, Benjamin; Ueno, Akira; Sakai, Tatsuo; Takanashi, Masahiro; Itabashi, Yu; Ota, Mie
Highlights: Frequency effect was studied in wide loading frequency range of 0.2 Hz to 20 kHz. Dislocation structures after usual and ultrasonic tests drastically differ. Slip band and fatigue crack initiation are also sensitive to the frequency. Such changes come from ultrasonic strain rate, in accordance with Seeger theory. Change of crack initiation mode is the main reason of longer fatigue at 20 kHz. Abstract: Fatigue properties of low carbon steels are known to be particularly sensitive to the loading frequency. Indeed, literatures related to this field usually point out an increasing fatigue life with an increase of the loading frequency. The authors of the present paper have already reconfirmed such a general phenomenon in the case of JIS S15C (0.15%C) low carbon steel. In that paper, S – N properties under usual frequencies of 0.2–140 Hz can be successfully normalized by the lower yield stress at the individual frequency. Nevertheless, some irregularities have been detected on the fatigue property at 20 kHz. In order to clarify the physical meaning of such irregularities, we will compare fatigue properties at usual frequencies and ultrasonic frequency. In this work, the former experimental results were reintroduced and new discussions were developed by performing additional experiments and analyses paying an attention to microstructure and dislocation structure. Thus, it was found that the loading frequency effect at ultrasonic frequency is due to a particular behavior of B.C.C. ferrite under high strain rate. Such a behavior causes strain inhomogeneities at grain boundaries, and then facilitates the intergranular crack initiation mode rather than the usual intragranular one often reported at lower loading frequencies. Longer ultrasonic fatigue lives at ultrasonic frequency are directly related to this transition of the crack initiation mode. In addition, effects of the pearlitic volume fraction on the fatigue behavior have been also discussed in the present work.